Perjalanan Sejarah dalam Naskah Kuno - Herwansyah, Herwansyah; Kulsum, Nyimas Umi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the representation of historical journeys in ancient Nusantara manuscripts through a qualitative approach, employing narrative structure analysis and hermeneutic interpretation. The objects of study—Babad Tanah Jawi, Hikayat Raja Pasai, and Kidung Sunda—were analyzed to reveal narrative patterns and the ideological functions of the texts. The findings indicate that these manuscripts do not merely record events but construct symbolic, ideological, and intertextual narratives of history. History is presented as a medium for shaping identity, legitimizing power, and preserving collective memory. These results broaden the approach to manuscript studies and offer new insights into how history is transmitted through local written traditions. Keywords: ancient manuscripts, historical narrative, hermeneutics, cultural identity, collective memory